ACCELERATED INDEPENDENT LEARNING BASED ON ISLAMIC VALUES: SPRITUAL INTEGRATION AND INNOVATION IN EDUCATION IN THE MODERN ERA - Aldi, Muhammad; Khairanis, Retisfa (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This article aims to explore the integration of Islamic values in Merdeka Belajar acceleration as an effort to increase the relevance of education to the needs of the times while strengthening the formation of students' spiritual character. This research uses a qualitative approach with literature study and document analysis methods, examining various Merdeka Belajar policies and their relationship with Islamic education principles. Data is collected through reviewing literature, educational policies, and sources related to Islamic values in the context of modern education. The analysis is carried out thematically to identify patterns of integration of Islamic values in Merdeka Belajar practices. The results showed that Merdeka Belajar provides a space for flexibility to integrate Islamic values, such as honesty, responsibility, and cooperation, in various aspects of learning. This program supports character building based on noble morals through a learning approach that is relevant to global challenges. However, the implementation of this integration still faces challenges, including a lack of in-depth understanding of Islamic values and limited teacher training. The implication of this research is the need for a more inclusive curriculum preparation, which is not only based on 21st century skill needs, but also strengthens spiritual and moral aspects. This research contributes to the development of a holistic educational concept, making Merdeka Belajar not only an educational reform, but also a tool for social transformation rooted in Islamic values.